Molecular Characterization of Cryptosporidium Oocysts in Samples of Raw Surface Water and Wastewater - Xiao, Lihua (American Society for Microbiology, 2001)
Recent molecular characterizations of Cryptosporidium parasites make it possible to differentiate the human-pathogenic Cryptosporidium parasites from those that do not infect humans and to track the source of Cryptosporidium oocyst contamination in the environment. In this study, we used a small-subunit rRNA-based PCR-restriction fragment length polymorphism (RFLP) technique to detect and characterize Cryptosporidium oocysts in 55 samples of raw surface water collected from several areas in the United States and 49 samples of raw wastewater collected from Milwaukee, Wis. Cryptosporidium parasites were detected in 25 surface water samples and 12 raw wastewater samples. C. parvum human and bovine genotypes were the dominant Cryptosporidium parasites in the surface water samples from sites where there was potential contamination by humans and cattle, whereas C. andersoni was the most common parasite in wastewater. There may be geographic differences in the distribution of Cryptosporidium genotypes in surface water. The PCR-RFLP technique can be a useful alternative method for detection and differentiation of Cryptosporidium parasites in water.